Differences In Activated Partial Thromboplastin Time (APTT) & Prothrombin Time (PT) Methods Point-of-Care Testing (POCT) and Electromechanic Semi Automatic - Mutiara Ayu Syifa; Dewi Indah Sari Siregar; Nindia Sugih Arto (GLOBAL HEALTH SCIENCE GROUP, 2026)
Currently, there are several methods of coagulation testing, one of which is the Point-of-care testing (POCT) method which has emerged as a tool that plays an important role in modern healthcare, enabling fast, convenient diagnosis as well as more economical costs and can be done directly at the patient's treatment site. Some laboratories have also used the semi-automatic elecromechanic coagulation analyser as a coagulation testing tool. Objective to see the difference of aPTT and PT values in POCT method and semi automatic electromechanic method, so that it is useful in the selection of coagulometer. This study is an observational study with a cross sectional design conducted at H. Adam Malik Hospital Medan. Using 100 samples obtained through non-probability sampling with the consecutive sampling technique, each sample was examined for aPTT, PT, and INR using the POCT method and the electromechanical semi-automatic method. The results of each examination were analysed using the Mann Whitney statistical test. The results of the comparative test between INR of the POCT method and electromechanic semi-automatic found a significant difference between the two examination methods (p = <0.001). While in the aPTT an PT parameter, the POCT method with semi-automatic electromechanic did not find a significant difference between the two examination methods (p = 0.434 and p= 0.371). The average value of the difference between the two tools was 4.12 seconds in aPTT parameters and 0.50 in INR. There is no significant difference in the results of the aPTT and PT parameter between the two methods but there is a difference in the results of the INR parameter.